Action Research: Bridging Theory and Practice in Social Sciences - Prachi Marwaha (AG Volumes, 2024)
This review paper examines action research, including its classification, stages, theoretical basis, principles, as well as practical applications. It investigates the classification of action research, delineates the cyclical stages of planning, action, observation, along with reflection, and delves into the theoretical underpinnings and fundamental principles that underpin this methodology. the paper emphasises the distinctive capacity of action research to reconcile the distance between theory and practice and the practice of action research across various disciplines. Through the integration of collaborative and reflective procedures, action research tackles real-world challenges while also adding to our theoretical and practical knowledge base.